RECONSTRUCTION OF LEGAL PROTECTION IN REALIZING SHARIA FINANCIAL INCLUSION BASED ON MAQASID AL-SHARI‘AH: THE PERSPECTIVE OF IBN ‘ASHUR - Adriandi Kasim; Evra Willya; Kartika Septiani Amiri; Sabbar Dahham Sabbar (Academic Bright Collaboration, 2026)
This study analyzes and reconstructs the legal framework for Islamic financial inclusion based on maqāṣid al-sharīʻah, from the perspective of Muḥammad al-Ṭāhir Ibn ʿĀshūr, motivated by Indonesia's persistently low Islamic financial literacy rate (9.14%, OJK SNLIK 2022). A normative juridical method is employed, drawing on statutory, conceptual, and philosophical approaches. Primary legal materials include Law No. 21/2008, Law No. 8/1999, Law No. 4/2023 (UU P2SK), POJK No. 6/POJK.07/2022, and DSN-MUI fatwas, analyzed qualitatively using Ibn ʿĀshūr's maqāṣid framework. Legal protection in Islamic finance is structurally deficient in three respects: regulatory fragmentation, formalistic Sharīʻah compliance, and inadequate disclosure standards. The low literacy rate creates information asymmetry that undermines genuine consumer consent (tarāḍī). Ibn ʿĀshūr's four principles, namely ḥifẓ al-māl, al-ʿadl, al-ḥurriyyah, and rafʿ al-ḥaraj, are operationalized as a four-pillar reconstruction model that integrates regulatory consolidation, substantive Sharīʻah supervision, Islamic financial literacy as a statutory obligation, and accessible dispute resolution. The framework carries normative implications for OJK, DSN-MUI, and Islamic financial institutions. As a normative study, empirical validation is not included; future socio-legal research is necessary to test the framework in practice. This study offers one of the more systematic attempts to operationalize Ibn ʿĀshūr's four universal principles into specific, enforceable legal protection standards for the Islamic financial sector.